Exploring the Impact of Employee Satisfaction on Organizational Performance: The Mediating Role of Rewards and Benefits - Muhammad Shayan; Hammad Zafar; Shaikh Muhammad Fakhr e Alam (Review Journal of Social Psychology & Social Works, 2025)
This research paper seeks to determine the relationship between the rewards and benefits provided to employees and the organizational performance with mediated variable of employee satisfaction. Studying causally and with a quantitative approach, the data was collected from 102 employees and managers from five different banks in Pakistan as Habib Metro, United Bank Limited, Bank Alhabib, Meezan Bank Limited, and Faysal Bank. The research propositions of the study are drawn from the sample hypothesis, and they assert that job satisfaction, ability utilization, working conditions, and creativity shape performance while rewards and benefits moderate the relationship between job satisfaction and performance. Psychometric properties were validated with Confirmatory Factor Analysis (CFA). Path analysis was used to utilize the structural and measurement model and examine the hypothesized connection. Lack of job satisfaction, utilization of skills, organizational working condition, and creativity were found to have significant impact on organizational performance. Additionally, it was established that while the rewards and benefits did partially help to explain the relationship between job satisfaction and organizational performance, they only did so to a certain extent. These studies imply that there is need to foster organizational climate and provide remuneration structures that increase Pasadena employees’ commitment and, in the long run, positive organizational outcomes. In view of the above findings, the study offers useful insights to managers and policymakers wanting to enhance organizational performance by selectively adopting best human resource practices